Size of Master Apical File and Optimal Irrigation of the Apical Zone: A Systematic Review - Aminoshariae, Anita; Kulild, James (Iranian Endodontic Journal, 2018)
Introduction: To determine what would be the minimal apical diameter for optimal chemomechanical preparation in the root canal system in terms of debridement and/or irrigation delivery, in patients undergoing nonsurgical root canal treatment. Methods and Materials: Randomized controlled clinical trials, cohorts, cross-over studies from peer-reviewed journals published in English from January 1950 to June 2018 which reported outcome in terms of healing, microbial reduction and/or effectiveness of irrigation delivery to the apical third of the root canal system. Two reviewers conducted a comprehensive literature search. There were no disagreements between the two reviewers. The articles that met the inclusion criteria went through a predefined review process. Results: Due to the variety of methodologies and different techniques used to measure outcome for master apical file enlargement, it was not possible to standardize the research data and to perform meta-analysis. Twelve clinical articles were identified that met the inclusion criteria. Conclusions: The overall level of evidence on this topic was moderate (fair). From this systematic review, the majority of the studies collected and referred to recommend sizes higher than #30 as the minimal size in order to adequately prepare the apical region of the root canals. Only 2 out of 12 studies suggested the size #25 as acceptable. From this systematic review it may be concluded that a larger MAF preparation above size 30 aids chemomechanical action. Keywords: Apical Size; Endodontics; Irrigation; Master Apical Size; Systematic Review